A decision support system to assess climate change impacts on rural communities - Luruli, Musiiwa Felicity (University of the Free State, 2016)
English: Climate change is likely to affect the way in which people live. Natural resources such as groundwater, surface water and wood form a vital component of the livelihood in rural communities and are used extensively in rural areas where basic services have not yet been provided. The effect of climate change on all these natural resource may impact the lives of those in rural communities. Climate change is already starting to affect some of the poorest and most vulnerable communities around the world. The aim of the dissertation was to develop a framework to assess the vulnerability of rural communities to climate change. This framework used the Millennium Ecosystem Assessment Conceptual Framework as a guideline, but also incorporated the results of face-to-face interviews conducted with members of a selected community. The purpose of the interviews was to interrogate the communities’ level of awareness on climate change and to gain an understanding of the parameters influencing the community’s vulnerability to the effects of climate change. The developed framework allows the calculation of a numerical value which represents the vulnerability of a community to climate change. To illustrate its application, the framework was used to assess the vulnerability of a selected community. In the same way, the framework can be applied to other rural communities in South Africa to assess their vulnerabilities and to prioritise those communities where funds and resources should be allocated when combatting the impacts of climate change. Further work to improve the framework developed in this study is recommended. These recommendations include: 1) considering other existing frameworks to better understand climate change impacts on rural communities and to strengthen and improve the assessment of the vulnerabilities faced by rural communities, 2) expanding the study to include more rural villages in order to better understand how other rural communities are affected by climate change and to establish recommendations which could assist in finding solutions on a wider scale for rural communities that are affected by climate change, 3) including in the framework adaptation measures to protect biodiversity and ecological parameters that support the livelihood of the community, and, 4) including long-term projection of the changes brought on by climate change to refine and improve the framework.

Afrikaans: Klimaatverandering sal waarskynlik die manier waarop mense leef affekteer. Natuurlike hulpbronne soos groundwater, oppervlakwater en hout vorm ‘n intrgrale deel van die lewensbestaan van landelike gemeenskappe, en word intens gebruik in landelike areas waar basiese dienste nog nie verskaf is nie. Die effek van klimaatverandering op al hierdie natuurlike hulpbronne mag impakteer op die lewens van mense in landelike gemeenskappe. Klimaatverandering is reeds besig om die armste en mees kwesbare gemeenskappe te affekteer. The doel van hierdie verhandeling was om ‘n raamwerk te ontwikkel om die kwesbaarheid van landelike gemeenskappe tot klimaatverandering te assesseer. Hierdie raamwerk gebruik die Millennium Ecosystem Assessment Conceptual Framework as riglyn, maar inkorporeer oof die resultate van aangesig-tot-aangesig onderhoude met die lede van die gekose gemeenskap. Die doel van die onderhoude was om die gemeenskap se bewustheid rondom klimaatverandering te toets en om ‘n begrip van die parameters te kry wat die kwesbaarheid van gemeenskappe tot klimaatverandering beïnvloed. Die ontwikkelde raamwerk laat die berekening van ‘n numeriese waarde toe wat die kwesbaarheid van die gemeenskap to klimaatverandering verteenwoordig. Om die toepassing van die raamwerk te illustreer, is dit gebruik om die die kwesbaarheid van ‘n geselekteerde gemeenskap te assesseer. Op dieselfde manier kan die raamwerk toegepas word op ander landelike gemeenskappe in Suid-Afrika om hul kwesbaarhede te assesseer en om daardie gemeenskappe te prioriseer waar fondse en hulpbronne toegeken moet word om die impakte van klimaatveradering te beveg. Verder werk om die raamwerk wat in hierdie studie ontwikkel is te verbeter word aanbeveel. Hierdie aanbevelings sluit in: 1) inagneming van ander bestaande raamwerke om die impakte van klimaatverandering op landelike gemeenskappe beter te verstaan, en om die assessering van kwesbaarhede deur landelike gemeenskappe getrotseer te versterk en te verbeter, 2) uitbreiding van die studie om meer landelike dorpies in te sluit sodat beter verstaan kan word hoe klimaat verandering landelike gemeenskappe affekteer en om aanbevelings te maak wat kan help om oplossings op ‘n groter skaal te vind vir landelike gemeenskappe wat geaffekteer word deur klimaatverandering, 3) insluiting in die raamwerk van aanpassingsmeganismes om biodiversiteit, asook die ekologiese parameters wat die lewensbestaan van die gemeenskate ondersteun, te beskerm, en, 4) insluiting in die raamwerk van lang-termynvoorspellings van die veranderinge deur klimaatverandering teweeg gebring om die raamwerk te verbeter en te verfyn.
Keywords: Dissertation (M.Sc. (Geohydrology))--University of the Free State, 2016; Climatic changes -- South Africa; Rural development -- South Africa; Groundwater; Natural resources -- South Africa; Land use, Rural -- South Africa